Tradisi Megibunng di Desa Padangbai Kecamatan Manggis Kabupaten Karangasem - Hellena Patiran; Ni Made Suriani; Luh Masdarini (Jurnal Kuliner, 2022)
AbstractThis research aims :(1) describe the application of the megibung tradition starting from the preparation session,  processing session, presentation session and completion of megibung in the village of padangbaiKarangasem district. (2) Describe manners in the megibung culture this type of research, the information analysis procedure used namely qualitative analysis. The result of this research show: (1) The implementation of the megibung tradition include a preparation for the megibung meal which is mode by the event organizer and the family guarded by the patus interpreter. In the processing session, the megibung dishes served are white rice, processed lawarnamely ,chikenlawar, processed satay namely skewered satay, and wrapped satay, babiguling, and jukutares in the sarving meal presentation session, the megibung meal contains gibungan which is placed in the bouquet is placed on the left and right sides of the flower and the megibung completion session is marked by clening the megibung area by the activity implementer. (2) Etiqutte in the megibungculture in padangbai village, karangasem district contains universal rules that are shown to all megibung participants while special rules are shown to everyone who participates in the megibung culture, all of these rules must be agreed, obeyed and carried out by all megibung participants because it has great religious values, etiquette and ultral values. Keywords :Eating etiquette, megibung, Tradition